O processo de formação das representações sociais de competência : um estudo entre profissionais da unidade central de administração de uma instituição federal de ensino - Morais, Pablo Augusto Panêtto de (2016)
The objective of this qualitative study is to understand the process of formation of social representations of competence for professionals working in the central unit of administration of a federal teaching institution. Data were obtained through focus g